Village-owned enterprises (VOEs) as agents of social entrepreneurship in West Sumatera: Examining entrepreneurial emotion and competitive advantage - Agriqisthi; Abdul Wahab, Nadratun Nafisah; Abdul Rahman, Rafiduraida (International Journal of Accounting, Finance and Business, 2025)
This study examines the role of Village-Owned Enterprises (VOEs) as social entrepreneurship agencies in West Sumatera, focusing on their entrepreneurial emotion factor and competitive advantage. This study adopts a quantitative approach, which includes descriptive analysis to elaborate on respondent characteristics and Structural Equation Modeling (SEM) analysis to test the instrument. This study found that entrepreneurial passion moderated the relationship between entrepreneurial alertness and bricolage, suggesting that emotional motivation is important in improving the effectiveness of resource use. In addition, the entrepreneurial bricolage has a positive and significant effect on VOEs competitive advantage, highlighting the importance of creative use of local resources. Entrepreneurial alertness also has a positive effect on VOEs competitive advantage, showing that the ability to identify business opportunities is essential. Finally, the entrepreneurial bricolage mediated the relationship between entrepreneurial alertness and VOEs competitive advantage, with entrepreneurial passion strengthening the relationship. The result of this study emphasizes the need for VOEs to utilize local resources innovatively to maintain their competitive advantage and contribute to local economic development.